Clinical swallowing assessment in the diagnosis of silent aspiration - Fabricio,Mariana Zerbetto (2020)
ABSTRACT Purpose: to identify, in the clinical assessment of swallowing, signs indicating silent aspiration in ischemic stroke patients. Methods: forty-six patients were assessed, 17 days being the mean time elapsed from the stroke to the swallowing assessment. The clinical assessment encompassed structural and functional aspects, oximetry monitoring, and cervical auscultation. During the videofluoroscopy examination, the patients were also monitored with pulse oximetry. In both assessments, the patients were given 100 ml of liquid. In the statistical analysis, the exact logistic regression test and odds ratio calculation were used, with a 0.05 significance level. Results: seven, out of the 46 patients, presented aspiration, which was silent in six of them. Change in the cervical auscultation, in the clinical assessment (OR: 18.8; 95% CI: 1.2 - 1000, p = 0.03), was associated with silent aspiration, as detected in the videofluoroscopy. The hawking present in the analysis of the recording (OR: 12.2; 95% CI: 1.23 - ∞, p = 0.03), was associated with possible non-silent laryngotracheal penetrations and aspirations. No change was identified regarding oxygen saturation in patients presented with silent aspiration. Conclusion: the change in cervical auscultation observed in the clinical assessment can indicate silent aspiration in patients affected by an ischemic stroke.